(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Kenya’s food insecurity hinders progress towards sustainable development. While the Kenyan Constitution guarantees every person the right to adequate food of acceptable quality, it also prohibits environmental and health endangerment. Whether and how to invest in genetically modified organism (GMO) technology as an alternative food production method is important. In this context, scientists should not be denied the opportunity of harmonising the tension between environmental safety and food security while upholding sustainable development. Scientifically, GMO crops are sustainable, notwithstanding the African Union’s rigid social and political setting. However, each state’s role in providing sufficient resources and law enforcement personnel is crucial. A GMO regulatory system addresses environmental safety and human health, explicitly adopting thedevelopmental risk notion. Kenya’s 2012 cabinet ban on GMO foods derived from the Séralini Report which erroneously claimed that GM maize causes cancer in rodents. The health ministry established a Task Force to review the country’s readiness regarding GMO safety and adoption. Despite having been completed in 2014, its Report remains secret. In 2015, the High Courtdismissed as premature demands for public participation on whether to unban GMOs. In 2022, President Ruto lifted the ban. Arguably, while permitting GMO experimentation, it is prudent to prescribe criminal sanctions. Beyond anthropocentric notions, green criminology provides a framework to analyse both illegal and legal environmental harms, and for appraising Kenya’s evolving GMO policy. The Constitution provides a right to sustainable use and also establishes enforcement mechanisms to compel cessation and restoration. Yet without punitive consequences, GMO regulations may not deter offenders from environmental contamination.